2008
DOI: 10.1253/circj.72.392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety of Drug-Eluting Stents in the Korea Acute Myocardial Infarction Registry

Abstract: tent implantation is an effective treatment for coronary artery stenosis and is a commonly used strategy in percutaneous coronary intervention (PCI). At the present time, 2 drug-eluting stents (DES: sirolimus and paclitaxel) have made it into large clinical trials and seem to have fundamentally changed the treatment of coronary artery disease. DES are successful in most patients in preventing restenosis as compared with bare metal stents (BMS). [1][2][3][4][5] There are reports of the superiority of the siroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The registry receives data from 41 primary percutaneous coronary intervention (PCI) centers in Korea. 16, 17 Between January and December of 2006, 5,421 patients were included and after exclusion of 848 patients who were younger than 20 years, who had visited the hospital more than 24 h after the onset of symptoms, or whose time of symptom onset or time of arrival to the first hospital was unclear, 4,573 patients were finally included in this study. The diagnosis of AMI was based on the clinical presentation, ECG findings and levels of cardiac enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…The registry receives data from 41 primary percutaneous coronary intervention (PCI) centers in Korea. 16, 17 Between January and December of 2006, 5,421 patients were included and after exclusion of 848 patients who were younger than 20 years, who had visited the hospital more than 24 h after the onset of symptoms, or whose time of symptom onset or time of arrival to the first hospital was unclear, 4,573 patients were finally included in this study. The diagnosis of AMI was based on the clinical presentation, ECG findings and levels of cardiac enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…The P value of the cumulative incidence of the composite of MACE comparing SES with BMS was 0.016 at 1 year, 0.036 at 2-years, and 0.06 at 3-year follow-up. KAMIR, 14,15,[21][22][23][24][25] launched in November 2005, is a population-based multicenter online data collection registry designed to reflect real-world practice in Asian patients presenting with AMI. The registry includes 50 community and teaching hospitals that enroll > 10,000 patients annually.…”
Section: Discussionmentioning
confidence: 99%
“…15 In South Korea, recent studies also showed that DES implantation in patients with AMI was clinically safe and that SES implantation in AMI patients was associated with a reduction of angiographic restenosis at 6 months compared with PES. 11,12 However, there are few studies comparing SES, PES, and ZES in AMI patients. In the present study, the mid-term angiographic outcomes of ZES appeared similar to those for PES (similar follow-up MLD, percent restenosis and late loss), except for the similar incidence of binary restenosis and greater late loss when compared with the SES group ( Table 3).…”
Section: Circulation Journal Vol73 December 2009mentioning
confidence: 99%
“…[8][9][10] However, recently the KAMIR (Korea AMI Registry) study group reported that the use of DESs in Korean patients with AMI was clinically safe and effective. 11 There is very limited information regarding the angiographic and clinical outcomes among the different DESs in patients with AMI undergoing PCI, especially DESs other than SES and PES. Park et al showed that SES implantation in AMI patients was associated with a reduction of angiographic restenosis at 6 months compared with PES.…”
mentioning
confidence: 99%